Could the postoperative residual of urine predict the outcome of TVTOmidurethral sling procedure in female patients?. (September 2019) - Bakas, P.; Betta, A.; Papadakis, E.; Liapis, E.; Klimis, N.; Deligeoroglou, E.
Abstract: Objective: To assess if the amount of postoperative postvoid residual of urine that is within the normal range (less than 100 mls) could predict the outcome of TVTO (Tension –free vaginal tape obturator) procedure. Study design: Second Department of Obstetrics and Gynecology, Aretaieio Hospital, University of Athens, Greece. Patients that had been submitted to TVTO procedure between 2013 and 2017 were reviewed and outcome was assessed.The follow up assessment included cough stress test, the Patient Satisfaction Questionnaire (PSQ), the Urinary Distress Inventory-6 (UDI-6) and the Patient Global Impression of Improvement (PGI-I) questionnaire. Results: The mean follow-up was 3.7 years (+1.35 years). Forty eight patients (40.3%) had only a TVTO procedure. Forty three patients (36.1%) had a TVTO procedure combined with anterior colporrhaphy. Twenty eight patients (23.6%) underwent a TVTO procedure and anterior colporrhaphy and posterior colpoperineorrhaphy. According to cough stress test 88% patients (105/119) were cured having a negative cough stress test. Using logistic regression analysis it was found that patient's age (p = 0.78), postoperative postvoid residual of urine ( = 0.24) or day of catheter removal (p = 0.22) had no statistically significant correlation with the medium term outcome of TVTO procedure. Also, regression analysis shows that patients' Body Mass Index (BMI) has negative correlation to the postoperative outcome. Conclusion(s): PVR < 50 mls appears to be related with successful medium term outcome after TVTO procedure. Also, patients' (BMI) has negative correlation to the postoperative outcome.